On the flow topology inside droplets moving in rectangular microchannels - Ma,S; Sherwood,JM; Huck,WTS; Balabani,S (Lab on a Chip, 2014)
The flow topology in moving microdroplets has a significant impact on the behaviour of encapsulated objects and hence on applications of the technology. This study reports on a systematic investigation of the flow field inside droplets moving in a rectangular microchannel, by means of micro-particle image velocimetry (μPIV). Various water/oil (w/o) fluid mixtures were studied in order to elucidate the effects of a number of parameters such as capillary number (Ca), droplet geometry, viscosity ratio and interfacial tension. A distinct change in flow topology was observed at intermediate Ca ranging from 10−3 to 10−1, in surfactant-laden droplets, which was attributed primarily to the viscosity ratio of the two phases rather than the Marangoni effect expected in such systems. W/o droplet systems of lower inner-to-outer viscosity ratios tend to exhibit the well-known flow pattern characterised by a parabola-like profile in the droplet bulk-volume, surrounded by two counter rotating recirculation zones on either side of the droplet axis. As the viscosity ratio between the two phases is increased, the flow pattern becomes more uniform, exhibiting low velocities in the droplet bulk-volume and higher-reversed velocities along the w/o interface. The Ca and droplet geometry had no effect on the observed flow topology change. The study highlights the complex, three-dimensional (3D) nature of the flow inside droplets in rectangular microchannels and demonstrates the ability to control the droplet flow environment by adjusting the viscosity ratio between the two phases.